2022
DOI: 10.1002/adom.202200862
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Based Integration of Vertically Stacked Organic Photodetectors Toward Easy‐To‐Fabricate Filterless Multi‐Color Light Sensors

Abstract: Solution‐processed, color‐selective organic photodetectors are uniquely positioned to deliver high‐performance, low‐cost, multicolor light sensors/imagers beyond the limitations of conventional, color‐filter‐based technologies. To realize such potential, however, a prominent challenge has been the solution‐based, monolithic integration of vertically stacked organic photodetectors, which would enable multicolor sensing with optimum light collection while benefiting from the scalability, cost, and sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 100 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…136 Zhao et al demonstrated the solution-based monolithic integration of vertically stacked OPDs. 137 They developed polymer-based photodetectors of F8T2:PCBM for blue color sensing and MEH-PPV:PCBM active layers for green color sensing (Figure 10a). Solution-processed poly(methyl methacrylate) was introduced as an insulating spacer between OPDs, which allowed the monolithic device to achieve independent bias and readout through the stacked photodetectors.…”
Section: Optical Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…136 Zhao et al demonstrated the solution-based monolithic integration of vertically stacked OPDs. 137 They developed polymer-based photodetectors of F8T2:PCBM for blue color sensing and MEH-PPV:PCBM active layers for green color sensing (Figure 10a). Solution-processed poly(methyl methacrylate) was introduced as an insulating spacer between OPDs, which allowed the monolithic device to achieve independent bias and readout through the stacked photodetectors.…”
Section: Optical Sensorsmentioning
confidence: 99%
“…Zhao et al demonstrated the solution-based monolithic integration of vertically stacked OPDs . They developed polymer-based photodetectors of F8T2:PCBM for blue color sensing and MEH-PPV:PCBM active layers for green color sensing (Figure a).…”
Section: Optical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their optoelectronic versatility, organic semiconductors enable narrowband photodetection through a variety of strategies, which can be grouped into three main classes: narrowband-absorption-type (NBA) [1,17,18]; filtered (including input optical filtering and internal filtering via charge collection narrowing, charge injection narrowing, or exciton dissociation); and microcavity-resonance-based [19][20][21][22]. Among these strategies, NBA photodetection has been mainstream due to its appealing trade-off between simplicity and performance, which is of fundamental importance for the realization of easy-to-make optoelectronics alternative to silicon-based technologies [6,19,23]. Specifically, an NBA photodetector consists of a sandwich-type device stack comprising a thin (∼100 nm) organic semiconductor layer, which selectively absorbs photons within the target spectral range [1,17,18] (figure 1(a)).…”
Section: Introductionmentioning
confidence: 99%
“…[6] The recent development of graphene-based, 2D, and halide perovskite photodetectors has not made much difference in terms of the dependency on applying filters or tuning the compositions of the compounds for wavelength-selective photodetection. [7][8][9][10] Therefore, filterless, wavelength-selective photodetection that can be realized on a monolithic material or single component Photosensors, photodetectors, or color sensors are key components for various optical and optoelectronic applications. Semiconductor-based photodetection has been a dominator which is excellent at measuring the photon intensity of incident light.…”
Section: Introductionmentioning
confidence: 99%